Social Policy or Structure? Income Transfers, Socio-demographic Factors and Poverty in the Nordic Countries and in France - Olli Kangas; Veli-Matti Ritakallio (Luxembourg Income Study (LIS), 1998)
The paper compares poverty in Denmark, Finland, Norway, Sweden and France. We answer whether it is justifiable to talk about a unified Nordic model in terms of poverty and poverty alleviation. We have (1) descriptive/analytical and (2) methodological goals. (1) We pool the four Nordic countries into a single data set and compare France with this 'Scandinavia'. The results give strong evidence to the existence of the homogenous Scandinavian model in terms of incidence of poverty, poverty profiles, and the effectiveness of social policy. (2) The methodological objective is to change the world and simulate what would happen if France had the Scandinavian social structure - but its own social policy - and vice versa. Our re-weighting simulations show that the 'Scandinavization' of France would almost eradicate poverty in France. The 'Francofication' of Scandinavia would cause dramatic results in Scandinavia: the number of persons totally dependent on social transfers would increase, the effectiveness of transfer systems would decrease, and the poverty rate would rise near to the actual French figures. In sum, the huge differences in the French and Scandinavian poverty rates are not mainly explained by income transfer programs but differences in the family structure and in labor market behavior. But it is important to remember that these patterns are greatly affected by the institutional set-ups of the welfare states.
Keywords: 330; Armutsbekämpfung; Policy-Mix; Wirkungsanalyse; Vergleich; Frankreich; Nordeuropa